Guidelines for Process Safety Hazard Assessment Based on Process Information - Husin, Muhammad Firdaus; Hassim, Mimi H.; Ng, Denny K. S.; Johari, Anwar; Kamaruddin, Mohd. Johari; Ngadi, Norzita (ITB Journal Publisher, LPPM ITB, 2018)
In any new chemical process development and design, process safety is a critical aspect to be considered besides economic and technical feasibility of the manufacture of the product. A lack of proper hazard assessment during the design phase may later result in accidents with disastrous consequences to workers, the public as well as the environment. Many methods have been introduced to qualitatively and quantitatively assess the safety level of processes. Despite the availability of a large amount of methods, a systematic framework that details guidelines for hazard identification, risk assessment, safety measure design, and safe critical decision-making is still missing. To address this issue, the main objective of this study was to propose a systematic framework that outlines comprehensive guidelines for assessing the safety performance of processes based on information from the piping and instrumentation diagram (P&ID). Apart from proposing the framework, appropriate strategies for minimizing safety hazards and risks are also recommended. In addition, the user is assisted in selecting the most appropriate assessment method according to his or her needs and the scope and constraints of the assessment. A case study is presented to illustrate the application of the proposed framework.